Evaluation of portal hypertension by real‐time shear wave elastography in cirrhotic patients. (5th May 2015) - Kim, Tae Yeob; Jeong, Woo Kyoung; Sohn, Joo Hyun; Kim, Jinoo; Kim, Min Yeong; Kim, Yongsoo
Abstract Background & Aims To assess the correlation between liver stiffness measurement (LSM) by real‐time shear wave elastography (SWE) and hepatic venous pressure gradient (HVPG) and to investigate the diagnostic performance of SWE for predicting clinically significant and severe portal hypertension (CSPH and SPH). Methods Clinical data of 115 cirrhotic patients with haemodynamic measurement were consecutively collected. Liver stiffness (LS) was measured using SWE by repeated performance five times per patient, and the median value and interquartile range of the parameters on the same day of HVPG measurement was calculated. CSPH and SPH were defined as a HVPG ≥10 mmHg and ≥12 mmHg respectively. Results A total of 92 patients (male, 63; mean age, 53 ± 11.9 years) were eligible for analysis. CSPH and SPH were detected in 77 patients (83.7%) and 66 patients (71.5%) respectively. HVPG were significantly correlated with LSM in the overall, CSPH, and SPH patients (r = 0.646, 0.574 and 0.424 respectively; all P < 0.001). With ascites, the correlation coefficient did not decrease (r = 0.587). The AUROCs of LSM was 0.819 (95% CI, 0.725–0.892) for CSPH and 0.867 (95% CI, 0.780–0.928) for SPH. The cut‐off values for determining CSPH and SPH were 15.2 kPa (Sensitivity, 85.7%; Specificity, 80.0%) and 21.6 kPa (Sensitivity, 83.3%; Specificity, 80.8%) respectively. Conclusion In cirrhotic patients, LSM by SWE is highly correlated with HVPG value regardless of ascites. SWE is a new reliable non‐invasive diagnostic tool to predict CSPH and SPH, even in cirrhotic patients with ascites.